The impact of Distance Learning on Students' Interaction Changes of Junior High School 2 Kaliwiro - S.Pd., Musonef; Wasino, Wasino; Priyanto, Agustinus Sugeng (JESS (Journal of Educational Social Studies), 2020)
____________________________________________________________ The research objective was to analyze the impact of changes in distance learning interactions. The approach method was qualitative. The data collection techniques are observation, interviews, and documentation. The source and method triangulation were used as data validity techniques. The data analysis technique was done by collecting data, reducing data, presenting data, and verifying conclusions. The learning interactions of students before the pandemic period were: (1) Student learning interactions include the planning stage, the teaching stage, and the learning evaluation stage. (2) Forms of student interaction include learning cooperation, accommodation, competition. During the distance learning process, changes in interaction appear (1) Students who spend activities doing assignments, relaxing, helping parents, playing games, and hanging out with friends. (2) The teacher carries out the lesson planning; the learning application shares assignments to students and provides advice for students who are not disciplined. The impact of changes in distance learning interactions: (1) for students, experiencing shock, passive students, students looking for signals in various places, losses in the assessment. (2) for teachers, experiencing unprepared use of learning media, find it difficult to apply learning methods. (3) for parents, parents find it difficult to replace teachers' roles, forcing parents to be technology literate.